Anda di halaman 1dari 19

# Lesson 13

## How to find antiderivatives

We have three methods:
1. Basic formulas
2. Algebraic simplification
3. Substitution

Basic Formulas
If f(x) is

k
cos(kx)
sin(kx)
ekx
1
x
ax

then an antiderivative is

x n +1 except if n=1
kx (assuming the variable is x!)

1
n +1

sin(kx)/k
cos(kx)/k
ekx /k

ln x
ax /ln(a)

Algebraic Simplification
2
1 3
(
x
!
1)(
x
+
1)
dx
=
x
!
1
dx
=
3 x ! x+C
"
"

! (3x + 1) dx =
2

2
3
2
9 3
6 2
9
x
+
6
x
+
1
dx
=
x
+
x
+
x
+
C
=
3
x
+
3
x
+ x+C
3
2
!

x + x2
dx =
x

x (1 + x )
dx = ! 1 + x dx = x + 12 x 2 + C
x

Integrals by Substitution
Let u=g(x).

x sin(x 2 )dx

du
= g!(x) so du = g!(x) dx
dx

Let u=?

du

u = x 2 ! du = 2xdx

1
1
1
2
2
x
sin(
x
)
dx
=
sin(
x
)
2
x
dx
=
sin(
u
)
du
=
!
cos(
x
)+C
"
"
"
2
2
2
2

Antiderivative Practice
4t
t
2sin(3t)
!
e
+
4
dt Use basic formulas:
"

Problem 1

4t
t
2
1 4t
2
sin(3t)
!
e
+
4
dt
=
!
cos(3t)
!
+
3
4 e
"

1
ln(4 )

4t + C

z 2 + 2z
dz Simplify algebraically first, then integrate.
Problem 2 !
2
z
z2 + 2z
z2 2z
2
! z 2 dz = ! z 2 + z 2 dz = ! 1 + z dz = z + 2 ln z + C
Problem 3

6t
dt
2
4+t

## Make a substitution: Let u=4+t2, so du=2tdt.

6t
2t
1
2
dt
=
3
dt
=
3
du
=
3ln
u
+
C
=
3ln
4
+
t
+C
! 4 + t2
! 4 + t2
!u

Antiderivative Practice
Problem 4

2
dy Make a substitution: u=ln(ky), so du=dy/y.
y ln(ky)

2
2 1
2
dy = !
dy = ! du = 2 ln u + C = 2 ln ln(ky ) + C
y ln(ky )
ln(ky ) y
u

Problem 5 Find the particular function F(x) such that F'(x)=x2 and
the graph of F(x) passes through (1, 2).
The general antiderivative is ! x 2 dx = 13 x 3 + C
3
Then to find C, we must have F(1) = 13 1 + C = 2
Thus, C=5/3, and our function is F(x) = 13 x 3 + 53

## Solving Definite Integrals

Theorem: (Fundamental Theorem I)

## Or: If F is an antiderivative for f, then

Example
We determined using Simpsons Rule :
Now use the fundamental theorem:
An antiderivative for f(x)=3x + 5 is
So:

12

## 3x + 5 dx = F(12) - F(0) = 276 - 0 = 276

Example

x 3 dx

We have to
find an antiderivative;
evaluate at 3;
evaluate at 2;
subtract the results.

!2 x dx = x
3 3

1
4

4 3
2

= 14 3 " 14 2 =
4

## This notation means:

evaluate the function at
3 and 2, and subtract the
results.

81
4

## Dont need to include +C in our

antiderivative, because any
antiderivative will work.

Examples
"

2sin( x ) + 3x dx

3x 2
2sin( x ) + 3x dx = \$2 cos x +
2

Alternate notation

=1
!

=1

"
3! 2 #
= % \$2 cos ! +
\$ (\$2 cos 0 + 0 )
&
2 (
'
"
3! 2 #
3! 2
= % \$2( \$1) +
\$ (\$2(1) + 0 ) = 4 +
&
2 (
2
'

1
"!2 s ds
!1

1
"!2 s ds = ln s
!1

!1
!2

= ln1 ! ln 2 =!! ln 2

Practice Examples
!

1
4
dx =
e
e

3 s ds =

3s ds = 2 s
1/ 2

3/ 2

9
2

()

=2 9

3/ 2

()

"2 2

3/ 2

= 54 " 4 2

ses + 1
"!2 s ds
!1
!1
1
s
s
= " e + ds = (e + ln s ) !2 = e!1 + ln1 ! (e!2 + ln 2)
!2
s
1 1
=!! ! 2 ! ln 2
e e
!1

## Substitution in Definite Integrals

We can use substitution in definite integrals.
However, the limits are in terms of the original variable.
We get two approaches:

## Solve an indefinite integral first

Change the limits
Method I:
First solve an indefinite integral to find an antiderivative.
Then use that antiderivative to solve the definite integral.
Note: Do not say that a definite and an indefinite integral are equal
to each other! They cant be.

Example
First: Solve an indefinite integral.

3t
3
dt =
2
t +4
2

2t
3
dt =
2
t +4
2

u=t2+4

3t
dt
2
t +4

du= 2tdt

1
du = 32 ln t 2 + 4 + C
u
Heres an
antiderivative!

2tdt
becomes du

and put in a 2.

3t
dt =
2
t +4

3
2

ln t + 4
2

## Heres the antiderivative

we just found.

) (
2

3
2

) (

ln 8 "

3
2

ln 5 = 23 ln 85

Example
When discussing population growth, we worked backwards to find out
what we got from evaluating

P!(t )
Lets find an antiderivative using substitution. "
dt
P (t )

"

P !(t)
dt =
P(t)

"

u= P(t)
du= P'(t)dt

1
du = ln u + C = ln P(t) + C
u

## Of course, P(t) is always non-negative, so we dont need absolute

values
\$ P(b) '
P !(t)
b
)
So we get: "a
dt = ln(P(t)) a = ln (P(b)) # ln (P(a)) = ln&
P(t)
% P(a) (
b

## Method II: Convert the Limits

Just put a and b into the substitution formula and get new limits.
Note: You do not have to go back to x then!
2
3t
Example !1 2
t +4

u = t2 + 4
du= 2tdt

8
3t
3 2 1
3 81
3
3
8
dt
=
2
t
dt
=
du
=
ln
u
=
ln
(
)
2
2
5
!1 t 2 + 4 2 !1 t 2 + 4
5
2 !5 u
When t=1, u=5.
becomes du
becomes u
When t=2, u=8.
What happens to t=1?
And when t=2,
2
u=t2+ 4 = 1^2+4= 5. u=t + 4 = 2^2+4= 8.

Example
!

( 5 y )dy
2

( 5 y )dy = )
3

u=5y2

y= 1: u=5

du=10ydy

y=8: u= 320
4
3

1
1
320
1 8
1
1 u
y (5 y ) dy = ) (5 y 2 )3 10 y dy = ) u 3 du =
10 1
10 5
10 4
3

## Note that we can also do

this problem without u-sub
--try algebraic simplification

1
2 3

320

4
4
"
3 !
= % 320 3 # 5 3 & \$ 163.5
40 '
(

5y

) dy = ! y (5y )
8

1
2 3

1
5
" 1 2%
8
dy = ! \$ 53 y 3 ' y dy = 53 ! y 3 dy
1
1
#
&

8
1
3

5
+1
3

1
8
8
y
3
=5
= 53 (8 3 ( 13 ) ) 163.5
5
8
+1
3
1

e4 x

Practice Example

dx

1+ e
Method I: Firstly compute
0

4x

u = 1 + e4 x
du = 4e4 x dx

e4 x
1 + e4 x

e4 x

1+ e

4x

dx
1
"
2

1
" +1
2

1
4e4 x
1 1
1
1 u
dx = !
dx = !
du = ! u du =
+C
1
4 1 + e4 x
4
4
4
u
" +1
2

1 12
1 + e4 x
= u +C =
+C
2
2

e4 x
1 + e4 x

dx =

1
1
1
1
1
1 + e4 x |10 =
1 + e4 "
1 + e0 =
1 + e4 "
2
2
2
2
2
2

Method II:

4x

1 + e4 x

dx =

4x

1
"
2

1
" +1
2

1 1 4e
1 1+ e 1
1 1+ e
1 u
1+ e4
dx
=
du
=
u
du
=
|
2
4 !0 1 + e4 x
4 !2
4 !2
4 1
u
" +1
2

1 12 1+ e4
1 + e4
2
= u |2 =
"
2
2
2

## Using Definite Integrals

We can now evaluate many of the integrals that we have been able
to set up.
Example
Find area between y = sin(x) and the
xaxis from x=0 to x=, and from
x=0 to x=2.
The area from 0 to is clearly:

0

## The area from 0 to 2 is more complicated. We note that

But this is obviously not the area!
The area from 0 to 2 can be found by:

2!

)(

2!

## sin( x ) dx " # sin( x ) dx = " cos( x ) 0 + cos( x ) !

!

)= 4

"

2!

sin( x ) dx =0

Summary
Used the fundamental theorem to evaluate
definite integrals.